Bactérias endosporogênicas no manejo de doenças do algodoeiro - Ferro, Henrique Monteiro (2009)
The cotton cultivation requires intensive pest control to ensure good productivity and consequent profitability to the farmer. Thus, there is need to develop alternative disease control methods for the rational fungicide use. Therefore, this study aimed to evaluate 4 sporogenic bacterial isolates (Bacillus subtilis UFLA285, B. subtilis ALB629, Bacillus spp. UFLA401 and Paenibacillus lentimorbus MEN2) in the control of major cotton foliar diseases: ramulosis (Colletotrichum gossypii var. cephalosporioides), bacterial blight (Xanthomonas campestris pv. malvacearum), alternaria leaf spot (Alternaria sp.), the soilborne white mold (Sclerotinia sclerotiorum) or boll rot (pathogen complex). We evaluated different application forms of isolates from trials from 2007 to 2009, under greenhouse and field conditions. In greenhouse, all isolates were effective in control of bacterial blight and ramulosis, especially UFLA285 which provided better control of bacterial blight. In the field, all isolates were effective in control of white mold, ramulosis and boll rot. Isolates UFLA285, ALB629 and MEN2 provided better control of white mold, boll rot and alternaria leaf spot. The combination of the three antagonistic isolates provided better control of ramulosis and increased productivity in the field, and the highest fiber percentage. Sporogenic isolates assessed in greenhouse showed different control levels of ramulosis and cotton bacterial blight on the method of application, except UFLA401 which did not differ among the forms of application in the control of ramulosis. In the field, the best method and number of antagonist applications s was the seed treatment + 2 sprays for ramulosis control. UFLA285 did not differ in the method of application in the control of the boll rot under field conditions. Therefore, based on the consistency of results obtained in the repetitions of the trials, the isolates have great potential in cotton integrated disease management.